Study on performance of flat and elongated aggregate in low traffic road - Nur Syazwani, Md Zaki (2010)
Aggregate are the largest amount of material that can be found in HMA. Aggregates make up between 80% to 90% of total volume or 94% to 95% of the mass of hot mix asphalt (HMA). With this facts, it is totally agree that aggregate properties are very important in HMA because it will affect the performances of the HMA. The objectives of this research are to evaluate the performances of the pavement using flat and elongated aggregate as the main material and to compare the strength of using flat and elongated aggregate in pavement mixes for low traffic road with the normal mixes. During the first stage, the aggregates were tested in order to know the characteristic. The test that had been done were AIV Test, ACV Test, LA Abrasion Test, Flakiness Index and Elongation Index. The bitumen also had been tested with the Penetration Test and Softening Point Test. After that, the mixtures were designed and prepared. The mixtures were designed as ACW14 and were tested in accordance with the JKR Specification:Arahan Teknik Jalan. 15 samples were prepared using Marshall Mix Design methods in order to determine the optimum asphalt content (OAC). The second stage of the research was to evaluate the performances of the mixture consist of flat and elongated aggregates. 12 samples were prepared with different percentage of flat and elongated aggregate which is 0% as the standard mixture, 20%, 40% and 60% as the experimental mixture. Based on the results, it is observed that flat and elongated aggregate might implies a significant effect on the performance of the mixtures. Thus, it can be concluded that the flat and elongated aggregate can be used in pavement mixtures but the percentage of aggregate must be limited to certain level to make sure the strength characteristics of the mixes can be maintained.